2017
DOI: 10.1002/slct.201701717
|View full text |Cite
|
Sign up to set email alerts
|

Push‐Pull N‐Annulated Perylene‐Based Sensitizers for Dye‐Sensitized Solar Cells: Theoretical Property Tuning by DFT/TDDFT

Abstract: We evaluate the effects of donor and π‐linker moieties on power‐conversion efficiency for a series of push‐pull type, N‐annulated perylene dyes for dye‐sensitized solar cells. Triphenylamine and diphenylamine are used as electron donors. We investigate the structural, optical, and electronic properties of dyes by performing density functional theory (DFT) calculations at the B3LYP level, using the 6‐311G(d,p) basis set. Electronic absorption wavelengths were investigated using time dependent DFT (TD‐DFT) calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The bandgap tuning in a system aiming at one specific emission wavelength is made possible by mere chemical substitution of appropriate electrondonating/withdrawing groups and is gaining interest in the field. [2][3][4][5][6][7] In general, a planar conventional organic luminescent system exhibits a good emission in a non-aggregated state than their aggregated state. [6,[8][9][10] Weak emissions in a planar molecule may be attributed to the presence of intense π-π stacking between the lattice planes.…”
Section: Introductionmentioning
confidence: 99%
“…The bandgap tuning in a system aiming at one specific emission wavelength is made possible by mere chemical substitution of appropriate electrondonating/withdrawing groups and is gaining interest in the field. [2][3][4][5][6][7] In general, a planar conventional organic luminescent system exhibits a good emission in a non-aggregated state than their aggregated state. [6,[8][9][10] Weak emissions in a planar molecule may be attributed to the presence of intense π-π stacking between the lattice planes.…”
Section: Introductionmentioning
confidence: 99%
“…26 Strategic architecture of desirable highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels in the active emitting layer is important for the rapid transfer of electrons and holes to the EML. [27][28][29][30][31] Functional metal-organic materials are an evolving class of luminophores as they include the benefits of both organic dyes, which are color-tunable with strong emission and transition-metal-based emitters with large Stokes shifts and high photostability. 32 These coordination complexes of organic molecules have been widely investigated for the development of electroluminescent devices that exhibit intense and bright fluorescence emission spanning the entire visible region from violet to red with high quantum efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Design strategies of active light emitters must result in the system possessing an optimal highest occupied and lowest unoccupied orbital energy levels to ease the charge injection and transport into the emissive layer. [11][12][13][14][15][16][17] Research development in this field has shown significant progress in the past few decades by a generation of different color emission, sweeping over the entire visible spectrum. [18][19][20][21][22][23][24][25][26][27] Despite steady progress, the efficient design of blue monochromatic luminophores functioning as active material in OLEDs remains a serious challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Precise bandgap engineering of an organic molecule achieved by various chemical routes has proven successful in the generation of desired fluorescent color emission. Design strategies of active light emitters must result in the system possessing an optimal highest occupied and lowest unoccupied orbital energy levels to ease the charge injection and transport into the emissive layer . Research development in this field has shown significant progress in the past few decades by a generation of different color emission, sweeping over the entire visible spectrum .…”
Section: Introductionmentioning
confidence: 99%